Analysis Of The Role Of The Deputy Principal For Student Affairs In Development And Improvement Intra-School Student Organization Work Ethos At SMAS St. Xaverius Gunungsitoli - Mendrofa, Elvienna Sally Juwita; Trisman Harefa; Riswan Zega; Kristof Marthin Telaumbanua (Visi Sosial Humaniora, 2024)
This study aimed to analyze the role of the Deputy Principal for Student Affairs in the development and improvement of the performance of the Intra-School Student Organization (OSIS) and in addition to analyzing what strategies were carried out by the Deputy Principal for Student Affairs in developing the work ethic of the Intra-School Student Organization (OSIS) at St. Xaverius Gunungsitoli SMAS. The method used was a qualitative approach with data collection techniques through interviews, observations, and documentation. There are 3 data analysis techniques used, namely: 1. Data Reduction, namely selecting and sorting the results of interviews to be more focused on the direction of research, 2. Data Display, namely describing the results of research using tables or charts, 3. Drawing Conclusions and Verification, namely providing conclusions from the results of interviews to be more relevant to the research results. The results showed that the Deputy Principal's role is very important in providing guidance, moral support, and administration needed to improve the performance of the Intra-School Student Organization (OSIS). In addition, the Deputy Principal's involvement in the activities of the Intra-School Student Organization (OSIS) contributes to the development of student leadership and increased participation in various school activities. The strategies provided by the Deputy Principal for Student Affairs to improve the performance of the Student Council were approaching or collaborating with other schools and also with teachers within the school, conducting evaluations, providing encouragement, motivation and suggestions to improve the performance of the Intra-School Student Organization. This study recommends the need for increased communication between the school and students to maximize the role of the Intra-School Student Organization (OSIS) in the school environment. Keywords: Deputy Principle for Student Affairs, Intra-School Student Organization (OSIS)